2015
DOI: 10.1161/circinterventions.114.001880
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of a Catheterization Laboratory–Only Eptifibatide Dosing Strategy in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Background-Eptifibatide, a small-molecule glycoprotein IIb/IIIa inhibitor, is conventionally administered as a bolus plus infusion. A growing number of clinicians are using a strategy of catheterization laboratory-only eptifibatide (an off-label use) as procedural pharmacotherapy for patients undergoing percutaneous coronary intervention although the comparative effectiveness of this approach is unknown. Methods and Results-We compared the in-hospital outcome of patients undergoing percutaneous coronary interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Fung et al [ 14 ] in the BRIEF-PCI trial, used a single bolus dose plus 2-h infusion of eptifibatide in low-risk patients undergoing PCI and found similar incidence of in-hospital MACE with no significant difference, but accompanied with significantly lower major bleeding, indicative of no need for prolonged infusion of eptifibatide, especially in low-risk patients. In another large study in 21,296 patients treated with eptifibatide, Gurm et al [ 15 ] showed that patients receiving eptifibatide bolus only had significantly lower rates of bleeding events and blood transfusion with no difference in adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Fung et al [ 14 ] in the BRIEF-PCI trial, used a single bolus dose plus 2-h infusion of eptifibatide in low-risk patients undergoing PCI and found similar incidence of in-hospital MACE with no significant difference, but accompanied with significantly lower major bleeding, indicative of no need for prolonged infusion of eptifibatide, especially in low-risk patients. In another large study in 21,296 patients treated with eptifibatide, Gurm et al [ 15 ] showed that patients receiving eptifibatide bolus only had significantly lower rates of bleeding events and blood transfusion with no difference in adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, the bolus only eptifibatide group had a significantly lower risk of bleeding (OR 0.74; p = 0.014), fewer gastrointestinal bleeds (OR, 0.40; p = 0.003), and less need for blood transfusions (OR 0.70; p = 0.012). 31 Therefore, bolus only GPI may preserve the ischemic benefits of GPI while reducing bleeding complications, although randomized studies are required for certainty.…”
Section: Bleeding Risk and Gpimentioning
confidence: 94%
“…A retrospective multicenter study comparing outcomes in patients receiving a bolus of eptifibatide ( n = 4511) versus a bolus followed by a maintenance infusion of eptifibatide ( n = 16,785) demonstrated no significant differences in stent thrombosis, target lesion revascularization, post‐procedure MI or death between the groups 31 . However, the bolus only eptifibatide group had a significantly lower risk of bleeding (OR 0.74; p = 0.014), fewer gastrointestinal bleeds (OR, 0.40; p = 0.003), and less need for blood transfusions (OR 0.70; p = 0.012) 31 . Therefore, bolus only GPI may preserve the ischemic benefits of GPI while reducing bleeding complications, although randomized studies are required for certainty.…”
Section: Intralesional Gpimentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Interventions, Gurm et al 14 add to the argument that the package insert dosing regimen of eptifibatide is an anachronism. Gurm et al 14 evaluate the in-hospital outcomes of a large cohort of patients at 47 hospitals treated with eptifibatide as an adjunct to PCI.…”
Section: See Article By Gurm Et Almentioning
confidence: 99%
“…Gurm et al 14 evaluate the in-hospital outcomes of a large cohort of patients at 47 hospitals treated with eptifibatide as an adjunct to PCI. The analysis was of data provided to the Blue Cross Blue Shield of Michigan Cardiovascular Consortium database.…”
Section: See Article By Gurm Et Almentioning
confidence: 99%